An iconic market place for Muar town - Law, Kher Choon (2017)
Providing node in Muar town allows local people to have their public activity. By constructing a new market place in an aging town, it could act as “magnet” to attract people to the place, bringing back vibrant and existing culture to the place, unite among the people and place together. At the same time, it reduces brain drain phenomenon especially during the age from 20 to 30, resulting the decrease of population in Muar town. An aging town had so-called as “retired town” or “dead town” by local people during the unstructured interview. Due to the lacking of public place, local people prefer to stay indoor rather than linger and mingle at outdoor. Observation shown that the town has become quiet and peaceful after dinner time, similarly to weekend, as local people prefer to drive to Melaka for night life, which is not far from Muar. The aim of this research is to create a new node for Muar town, by having suitable market place for local people to carry out their public activity. By having spice and herb market, it could revive the identity of the place, as spice and herb were the main economy that generate income from the past, develop Muar into a small town. The new market place also creating a new iconic image in Muar town, not only to attract local people to the place, but also attracting tourists from different places. A new node could also create sustainability to the place, as the research examines that local people and economic activities could bring prospect and possibility to the upcoming growth in Muar town. The focus target user would be the elderly people, as during the site observation, majority of elderly were found to be linger around as long as there is a gathering place. The findings covered the site observation, ethnographic study, unstructured interview, case study and questionnaire for collection data about the place. As a result, existing nodes in Muar town such as morning wet market and Food Street would be the focused for the discussion in order to understand deeper about the culture of the place. Later, the significance elements of existing nodes will be applied as design strategy and create a new iconic image for Muar town.